Phytochemical screening & in-vitro evaluation of anti-inflammatory activity of clerodendrum indicum roots (World Journal of Current Medical and Pharmaceutical Research, 2021)
This study aims to extract the phytochemical constituents and in-vitro evaluation of   anti-inflammatory activity of roots of clerodendrum Indicum. Clerodendrum indicum (L.) kuntz. Commonly known as bharangi or chingari, belongs to the family verbenaceae. The plant is expectorant, stomachic, Anti-bronchitis, Anti-nociceptive, Anti-microbial, Anti-diarrheal, anti-oxidant and anti-cancer. Preliminary phytochemical screening revealed the presence of flavonoids, steroids, steroid glycosides, terpenoids etc. This study has taken with the Anti-inflammatory  activity and preliminary phytochemical screening on the clerodendrum indicum. In the present study, qualitative study of    the phytochemicals present in the sample was determined, Anti-inflammatory  activity  were carried out. On the premise of the prevailing study, the outcomes eventually concluded that the ethanolic extract of clerodendrum indicum own anti inflammatory pastime. This evaluation offers an concept that the compound of the plant clerodendrum indicum may be used as lead compound for designing robust pills which may be used for remedy of diverse diseases.